Synthesis and Structural Analysis of Magnesium Oxide Nanomaterial Using Ethanol as Polymerization Solvent - I Wayan Sutapa; Abdul Wahid Wahab; Paulina Taba; Nursiah La Nafie (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2019)
The purpose of the study was to synthesize MgO nanomaterials using sol-gel method with ethanol as solvent and to perform structural analysis of the products. Mg-oxalate was initially prepared prior magnesium acetate. Magnesium acetate dissolved in ethanol, and the oxalic acid added to adjust pH until gel phase formed. The gel was heated at 100 C for 24 hours to produce magnesium oxalate solids. Solids was sieved using ±150 mesh then annealed at 550 C for 6 hours to produce MgO nanomaterial. The magnesium oxalate was characterized using FT-IR, XRD, and SEM. FT-IR peak at 3408.22 cm-1; 1709.35 cm-1; 1375.39 cm-1; 830.32 cm-1; 420.48 cm-1, and the XRD peak 17.95o; 22.97o; 25.02o; 27,94o; 35.10o; 37,63o; 44.16o were characteristic of Mg-oxalate. Meanwhile, FT-IR band at 1030.24 cm-1; 2358.94 cm-1; 1627.92 cm-1; 1417.66 cm-1; 437.84 cm-1, and XRD peak at 38.92o; 43.3o; 56.02o; 62.64o; 74.88o and 79.04o shows characteristic of MgO nanomaterial. Structure analysis shown the MgO nanomaterials has an average crystal size 8.11 nm, and lattice length 21.21 nm. The values of strain, stress, energy density crystal and dislocation density of the MgO are 5.3 x 10-5 MPa, 32.97 MPa, 154.81 J/nm2, 1.52 x 10-3 nm-2 respectively. Morphologically the MgO nanomaterial produced is cubic.